Influência da LLLT (GaAlAs) com diferentes energias na Movimentação ortodôntica em ratos - Torri, Simone (2013)
Introduction: Prolonged treatment times are one of the greatest challenges of orthodontic practice. Research has shown that laser therapy can be used as an adjunct to orthodontic movement, with effects on bone repair and analgesia. This study sought to assess the influence of low-level laser therapy (LLLT), using different energy settings, on orthodontic tooth movement in rats. Methods: Twenty-five male Wistar rats were randomly allocated across four different energy setting groups and one control group. A 10-g load was applied to the left maxillary first molar. During orthodontic movement, 830-nm laser radiation was administered to three spots at different energy settings depending on group allocation (12J, 15J, 18J, or 21J per site). Orthodontic movement was measured throughout the experiment and calcein dye was injected into the specimens for measurement of the area of neoformed bone. Conclusions: At the energy settings and protocols used in this study, LLLT does not appear to influence the rate of orthodontic movement, although different energy settings encourage bone neoformation.